Analysis of PAD, Investment, and Transfer Funds on Public Spending and Economic Growth in East Java - Ma’ruf, Muhammad; Sumarsono, Hadi (Jurnal Ekonomi Balance, 2024)
Economic growth is measured through various indicators that can depict the economy of a region. The purpose of this research is to seek knowledge about the influence of regional original income (PAD), investment, and transfer funds on public expenditure, as well as the economic development of East Java for the period 2017-2021. The method used is quantitative descriptive, and path analysis is employed on panel data. The research is conducted using secondary data obtained from the Ministry of Finance and BKPM, which includes time series data for the period 2017 to 2021 and cross-sectional data consisting of 38 cities/districts, hence referred to as panel data. The results of the research indicate that the variables of regional original income (PAD) and transfer funds have a significant influence on public spending. However, the investment variable does not have a significant impact on public expenditure. Regional original income and investment have a significant impact on economic growth. On the other hand, public spending and transfer funds do not significantly affect economic growth.